Microscopic Observation of the Brittle-Striation Formation Mechanism in Low Carbon Steel Fatigued in Hydrogen Gas (TEM and EBSD Observation Corresponding to Fractography) - Nishikawa, Hide-Aki; Oda, Yasuji; Takahashi, Yoshimasa; Noguchi, Hiroshi (Journal of solid mechanics and materials engineering, 2011)
Observations by Transmission Electron Microscopy and Electron Backscatter Diffraction corresponding to Fractography were conducted in order to investigate the brittle-striation formation mechanism of low carbon steel JIS S10C in a hydrogen gas environment. The main results are as follows: (1) The quasi-cleavage (QC) facets plane with brittle-striations does not coincide with the (100) cleavage plane. (2) Slip deformation distributions reflecting the brittle-striation formation processes are observed by TEM. One of the conceivable brittle-striation formation mechanisms which can explain these results is as follows. A striation line is formed during the loading part of the cycle as a trace of blunting by slips. A stable ductile crack then starts growing. These processes are similar to those in the normal ductile fracture from a crack; that is, a ductile tearing process in tension.